Foul Play - Reade, Charles, 1814-1884; Boucicault, Dion, 1820-1890 (Salt Lake City, UT : Project Gutenberg, 2003)
"Foul Play" by Charles Reade and Dion Boucicault is a dramatic novel written during the mid-19th century. The book centers around the lives of two families, the Wardlaws and the Penfolds, as it delves into themes of trust, betrayal, and the consequences of a single mistake. The narrative begins with the relationship between father and son, John and Arthur Wardlaw, and hints at impending turmoil involving characters from both families. The opening portion introduces us to Mr. Wardlaw's formal dining room, where a tense silence between father and son foreshadows matters of great importance that they are unable to discuss due to the watchful presence of their servants. Arthur, who has recently passed his university examination, is on the cusp of entering a partnership in his father's business. However, the plot quickly thickens when Mr. Christopher Adams appears, revealing that a forged note linked to Robert Penfold, the son of the Wardlaws' loyal cashier, threatens to unravel the ties between both families. As Arthur struggles with the implications of his friend$1 (Bs potential wrongdoing, it becomes clear that loyalty and justice will be pivotal themes as the story unfolds. (This is an automatically generated summary.)s
Release date is 2003-02-01
Produced by James Rusk. HTML version by Al Haines.
Keywords: Islands -- Fiction; Love stories; Clergy -- Fiction; Forgers -- Fiction; Shipwrecks -- Fiction